Digitalization of public diplomacy: Concepts, trends, and challenges. Issue 4 (December 2022) - Manor, Ilan; Huang, Zhao Alexandre
Dr. Ilan Manor is a leading scholar in the digitalization of public diplomacy and a senior lecturer at the Ben Gurion University of the Negev. From the beginning of his academic career, Dr. Manor invested in researching the digitalized practices and strategies of the Ministries of Foreign Affairs and conceptualized the expression "the digitalization of public diplomacy" to explore how digital technologies shape the norms, values, and working routines of diplomats and diplomatic institutions. Based on the hypothesis of transparency as the core of social media technology, Dr. Manor mentioned that diplomacy has also had to become more open, especially in public diplomacy. Traditional secret diplomatic negotiations are under universal scrutiny by netizens because they are digitalized. Thus, the public wants diplomats to be more open and transparent in their professional activities. However, digitalization also brought a series of communication problems, especially in the time of geopolitical uncertainty of the COVID-19 pandemic and the Russia-Ukraine war. In the academic dialogue, Dr. Manor has analyzed the conceptualization, practices, and challenges of the digitalization of public diplomacy in the framework of the current geopolitical context and global crisis and reviewed the long-term conceptual debate in public diplomacy scholarship on the value of soft power in the digital age. The last part of this dialogue focused on using visual supports in the international communication arena, criticizing the omnipresent use of memes and gifs of the Russian and Ukrainian governments during the war and questioning the public(s) in the digitalization of public diplomacy.